2017
DOI: 10.1021/acs.jafc.7b05026
|View full text |Cite
|
Sign up to set email alerts
|

Small Peptides Isolated from Enzymatic Hydrolyzate of Fermented Soybean Meal Promote Endothelium-Independent Vasorelaxation and ACE Inhibition

Abstract: Fermentation of soybean is a process in which soy proteins are broken down into small peptides to exert various physiological functions beyond their nutritional value and to improve food source bioactive components responsible for health benefits. Enzymatic hydrolysis could speed up the degradation of proteins during fermentation of soybean, thus resulting in higher peptide production. In the present study, fermented soy meal (fermented with Bacillus subtilis from Douchi) was hydrolyzed by thermolysin, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
(57 reference statements)
1
20
0
Order By: Relevance
“…The improved fibre digestion in SBM-fed lambs could also be an effective factor in improving gain. Soybean meal is a protein source which could produce relatively high peptide levels (Wang et al ., 2017). Addition of a peptide source in continuous culture has been reported to increase branched chain volatile fatty acid (BCVFA) production (Griswold et al ., 1996), which has potential for increasing fibre digestion (Gorosito et al ., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The improved fibre digestion in SBM-fed lambs could also be an effective factor in improving gain. Soybean meal is a protein source which could produce relatively high peptide levels (Wang et al ., 2017). Addition of a peptide source in continuous culture has been reported to increase branched chain volatile fatty acid (BCVFA) production (Griswold et al ., 1996), which has potential for increasing fibre digestion (Gorosito et al ., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this study was to produce new miso with hypotensive effects by modifying the fermentation process. Many studies have reported that there is ACE inhibitory activity in enzyme-hydrolyzed fermented soybean or dipeptides derived from soybean [17][18][19]. To our knowledge, however, there have been few studies in vivo on the involvement of ACE inhibition in BP reduction by miso.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of antinutritional factors can be decreased and the nutritional value can be improved by adding fibrolytic enzymes and lactic acid bacteria to the fermentation process (Cheng et al, 2019). By such treatments, the protein of soyabean meal can be degraded into numerous kinds of small peptides by fermentation, as well as the content of angiotensin-converting enzyme can be increased to ensure animal health (Wang et al, 2017). After the co-fermentation and decomposition by Lactobacillus plantarum, Bacillus subtilis and Saccharomyces cerevisiae, soyabean meal can be widely used in piglet feeding without affecting the daily gain of piglets, but augmenting their immune ability and promoting the development of small intestinal epithelial cells (Zhu et al, 2017).…”
Section: Purpose Of Microbe and Enzyme Cooperationmentioning
confidence: 99%